(untitled) (Fiep Bulletin - online, 2024)
Introduction: The COVID-19 pandemic is a global challenge, marked by uncertainties in prevention and therapeutic management. Objective:This study aimed to describe case studies and investigate how institutional, organizational, governance and political (IOGP) factors influenced decision-making and implementation of public health interventions in Southern Brazil. Methods: Retrospective case studies were conducted using data from state and national health websites in 2020-2021. Data on mortality and cases relating to the population were analyzed and the impact of climatic and cultural aspects on the spread of the pandemic was assessed. Results:The results revealed different dynamics of COVID-19 in the states of the Southern region, often marked by limited commitment from both the population and state authorities. As cases fell, restrictions were eased, promoting a return to normality. Analysis of the determinants of COVID-19 highlighted the interplay between unemployment, education, and state-specific policies. Factors such as inadequate sanitation, limited access to education and healthcare, crowded public transport and challenges associated with isolation have contributed to the transmission of the virus. Conclusion:In summary, this study highlights the influence of IOGP factors in shaping responses to the pandemic, with variations in results and public commitment observed among the states in southern Brazil. Addressing factors such as basic sanitation and access to education is crucial to mitigating the impact of the virus and promoting better public health outcomes.